2020
DOI: 10.21037/atm-20-3332
|View full text |Cite
|
Sign up to set email alerts
|

Skin melanoma survival is not superior in females in the new stage IIID of the 8th edition of the staging system: an analysis of data from the Surveillance, Epidemiology, and End Results (SEER) database

Abstract: Background: In the 8th edition of the melanoma staging system, stage III was divided into stages IIIA-IIID. Previous studies have found that the long-term survival rate of females is much higher than that of males. This study was designed to explore whether this sex-specific advantage still exists in the new staging subgroups.Methods: We obtained data from individuals diagnosed with skin melanoma between 2004 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database. A total of 8,726 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, once melanoma is diagnosed with central nervous system metastasis, its prognosis is abysmal (median OS is only 4 months) (23). The revision of the 8th edition of the AJCC (26,27). Moreover, our nomogram model suggested that stage IV CM patients without ulceration were better candidates for surgery for the first time.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, once melanoma is diagnosed with central nervous system metastasis, its prognosis is abysmal (median OS is only 4 months) (23). The revision of the 8th edition of the AJCC (26,27). Moreover, our nomogram model suggested that stage IV CM patients without ulceration were better candidates for surgery for the first time.…”
Section: Discussionmentioning
confidence: 90%
“…Ulceration status is defined based on histopathologic examination of the absence of the complete epidermal allodermis over any part of the primary tumor with associated host response, and both the seventh and eighth editions of the AJCC staging guidelines consider ulceration as an additional T-category criterion ( 4 , 25 ). Previous studies have shown that both breslow tumor thickness and ulceration are independent prognostic factors for OS in CM patients; therefore, we discussed T-staging into two variables: Breslow tumor thickness (T1, T2, T3, and T4) and ulceration (Yes and No) during the study ( 26 , 27 ). Moreover, our nomogram model suggested that stage IV CM patients without ulceration were better candidates for surgery for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk melanomas are associated with equal to or greater than 50% risk of recurrence or death in 5-year perspective [23]. The introduction of the 8 th AJCC melanoma staging system caused controversies, nonetheless, it allowed to divide more accurately subgroups at high risk of relapse and death from the heterogeneous stage III group [24,25]. The predicted 5-year OS in accordance with the 7 th AJCC staging system varied from 78% to 40% (IIIA-C) and after the 8th update from 93% to 32% (IIIA-D) [19].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Traditional prognostic factors for melanoma, including primary tumor thickness, ulceration, and age have been widely utilized for survival prediction. 14,[17][18][19] However, these factors may not fully capture the complexities associated with NM in the head and neck region. Therefore, there is a need to develop a survival prediction model that incorporates specific clinical and pathological characteristics relevant to NM in the head and neck.…”
Section: Introductionmentioning
confidence: 99%